2020
DOI: 10.1101/2020.06.05.20114876
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impaired Th17 immunity in recurrent C. difficile infection is ameliorated by fecal microbial transplantation

Abstract: Background & Aims. Clostridioides difficile is a leading cause of infectious diarrhea and an urgent antimicrobial resistant threat. Symptoms are caused by its toxins, TcdA and TcdB, with many patients developing recurrent C. difficile infection (CDI), requiring fecal microbiota transplant (FMT). Antibody levels have not been useful in predicting patient outcomes, which is an unmet need. We aimed to characterize T cell-mediated immunity to C. difficile toxins and assess how these responses were affected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 41 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…investigated how FMT affects CDI immunity. Patients with recurrent CDI have a reduced frequency of circulating TcdB‐specific CD4 + Th17 cells but not CD4 + Th1 and Th2 cells 153 (Fig. 1).…”
Section: Fecal Microbiota Transplant (Fmt) and The Immune Responses During CDImentioning
confidence: 96%
See 2 more Smart Citations
“…investigated how FMT affects CDI immunity. Patients with recurrent CDI have a reduced frequency of circulating TcdB‐specific CD4 + Th17 cells but not CD4 + Th1 and Th2 cells 153 (Fig. 1).…”
Section: Fecal Microbiota Transplant (Fmt) and The Immune Responses During CDImentioning
confidence: 96%
“…The authors found a small decrease in Th2 cells and a significant increase in the proportion of TcdB‐specific Th17 cells post‐FMT therapy. The effectiveness of the treatment was further demonstrated by the increase in the levels of anti‐TcdA, TcdB, and TcdBCROPS IgA and IgG in plasma samples from patients with recurrent CDI after FMT therapy 153 …”
Section: Fecal Microbiota Transplant (Fmt) and The Immune Responses During CDImentioning
confidence: 97%
See 1 more Smart Citation